Epidemiology and clinical course of severe acute respiratory syndrome coronavirus 2 infection in cancer patients in the Veneto Oncology Network: The Rete Oncologica Veneta covID19 study. (April 2021) - Guarneri, Valentina; Bassan, Franco; Zagonel, Vittorina; Milella, Michele; Zaninelli, Marta; Cattelan, Anna Maria; Vianello, Andrea; Gori, Stefania; Aprile, Giuseppe; Azzarello, Giuseppe; Chiari, Rita; Favaretto, Adolfo; et al.
Abstract: Introduction: Coronavirus disease 2019 (COVID-19) pandemic started in Italy with clusters identified in Northern Italy. The Veneto Oncology Network (Rete Oncologica Veneta) licenced dedicated guidelines to ensure proper care minimising the risk of infection in patients with cancer. Rete Oncologica Veneta covID19 (ROVID) is a regional registry aimed at describing epidemiology and clinical course of Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in patients with cancer. Materials and methods: Patients with cancer diagnosis and documented SARS-CoV-2 infection are eligible. Data on cancer diagnosis, comorbidities, anticancer treatments, as well as details on SARS-CoV-2 infection (hospitalisation, treatments, fate of the infection), have been recorded. Logistic regression analysis was applied to calculate the association between clinical/laboratory variables and death from any cause. Results: One hundred seventy patients have been enrolled. The median age at time of the SARS-CoV infection was 70 years (25–92). The most common cancer type was breast cancer (n = 40). The majority of the patients had stage IV disease. Half of the patients had two or more comorbidities. The majority of the patients (78%) presented with COVID-19 symptoms. More than 77% of the patients were hospitalized and 6% were admitted to intensive care units. Overall, 104 patients have documented resolution of the infection. Fifty-seven patients (33%) have died. In 29 cases (17%), the cause of death was directly correlated to SARS-CoV-2 infection. Factors significantly correlated with the risk of death were the following: Eastern Cooperative Oncology Group performance status (PS), age, presence of two or more comorbidities, presence of dyspnoea, COVID-19 phenotype ≥ 3, hospitalisation, intensive care unit admission, neutrophil/lymphocyte ratio and thrombocytopenia. Conclusions: The mortality rate reported in this confirms the frailty of this population. These data reinforce the need to protect patients with cancer from SARS-CoV-2 infection. Highlights: Patients with cancer represent a vulnerable population, with risk of severe complications. Active anticancer therapy does not increase the risk of death. The risk of death can be stratified according to clinical and laboratory parameters. Cancer services must adopt all preventive measures to protect patients from infection.